A study of the relationship and the incidence of renal failure disease is unknown reasons - Hmood, Baheeja Abees; Hashim, Huda Raheem (Al-Qadisiyah Journal of Pure Science, 2021)
This study was designed to detection the Relation ship between Ochratoxin A Renal fulier in patients suffer from Renal fulier attended to Al-Diwanyia teaching hospital in period from September 2012 to January 2014 ,These patients were diagnosed by physician in above hospital . By using Thin Layer Chromatography (TLC) the results showed (23.07%) from patients blood specimens had Ochratoxin A, (19.23 %) from patients urine specimens had Ochratoxin A,(38.46%) from patients had Ochratoxin A in blood and urine where only (19.23% ) your blood and urine were clear from above toxin ,So healthy persons were had Ochratoxin A in your blood and urine by rate ( 20 %) (40%) respectively and (10%) from them had Ochratoxin A in your blood andurine and only ( 30 %) from them don’t had Ochratoxin A in their blood and urine the concentration of chratoxin in blood were ranged between (6.2 -25 ) ng/ ml and ( 4-10.) ng/ ml in urine and in healthy reach concentration of Ochratoxin A in blood ( 2.3-3) ng/ ml and (4.3-4.) ng/ ml in urine. The data of this study showed the male highly infected (87.5%) with ocratoxin while in female ( 70%) and (71-80) years age had highly infected ( 92.85%) with ochratoxin A The results of study of biochemical parameter in patients showed highly raised in WBC and urea and Keratinin to reach to (1200 ) corpuscle /ml3, (310 )mg/dl , ( 12.2 ) mg /dl respectively and lowed the activity of alkaline phosphates enzyme and albumin into ( 2.2 ,1.5 )gm/dl . respectively and suger 120 mg /dl.